A Length-of-Season Analysis for Maize Cultivation from the Land- Surface Phenology Metrics Using the Sentinel-2 Images - Irena Rapčan; Dorijan Radočaj; Mladen Jurišić (Poljoprivreda)
This study analyzes the length of a growing season for maize cultivation in Osijek- Baranja County utilizing a land-surface phenology metrics derived from the Sentinel-2 imagery according to a normalized-difference vegetation index (NDVI). The three key phenological indicators were calculated, including the start of a season (SOS), end of a season (EOS), and the length of a season (LOS) for the years 2017 and 2022. The mean monthly air temperatures during the maize-growing season were significantly higher than the 30-year average, while a total precipitation was notably lower, particularly in August, suggesting a direct impact on maize phenology, with the LOS values exhibiting a non-normal distribution and differing variances between the years studied. This research contributed the insights for the improvement of yield forecasting and the adaptive management strategies in response to a climate variability, ultimately supporting food security and sustainable land management practices in the region. A future work should be expanded on these methodologies to enhance their applicability across the diverse agricultural contexts.